Step-by-step explanation:
How I figured this out is kind of plug in play with a bit of algebra, you want to get it to y = mx + b so to do that, you first need to set up your equation like (y - y1) = m(x - x1)
Plug in what you know:
(y - 4) = 1/2(x + 2) (notice I changed the x- x1 to x + x1 because x1 in this is a negative and subtracting a negative is the same as adding)
Then figure out what you don't know:
Distribute 1/2 to x and -2
(y - 4) = 1/2x -1
add 4 on both sides to leave y by itself
<u>y = 4.5x + 3</u>
Therefore your answer should be <u>y = 4.5x + 3</u>
Let me know if I got it wrong please
Hope this helps! <3